2015
DOI: 10.4103/0973-1482.147692
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression is associated with elevated aspartate aminotransferase level in hepatocellular carcinoma

Abstract: COX-2 expression may be involved in HCC carcinogenesis with high specificity for disease detection. COX-2 expression is significantly associated with elevated AST levels indicating a mechanism that may correlate both markers. However COX-2 expression seems to be an independent factor with no correlation to any of the histopathological data or patient's survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The carcinogenetic effects of COX-2 have been studied in cancers of various organs such as breast, 11 lung, 12 esophagus, 13 head and neck, 14 bladder, 15 and liver. 16 Cyclooxygenase-2 has also been found to be over-expressed in CRC. 7 , 9 , 17 This role of COX-2 in the human malignancies, including CRC was discovered by recent epidemiological studies, which reported an approximately 50% decrease in the relative risk of CRC in individuals using non-steroidal anti-inflammatory drugs; suggesting that these drugs might have protective and therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The carcinogenetic effects of COX-2 have been studied in cancers of various organs such as breast, 11 lung, 12 esophagus, 13 head and neck, 14 bladder, 15 and liver. 16 Cyclooxygenase-2 has also been found to be over-expressed in CRC. 7 , 9 , 17 This role of COX-2 in the human malignancies, including CRC was discovered by recent epidemiological studies, which reported an approximately 50% decrease in the relative risk of CRC in individuals using non-steroidal anti-inflammatory drugs; suggesting that these drugs might have protective and therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins synthesized by the cyclooxygenase (COX) pathway, act as mediators of inflammatory and immunological reactions [ 21 ]. Recent studies demonstrated that high expression COX2 are closely related to carcinogenesis[ 41 ]. However, evidence that changes of prostaglandins occur in patients with hepatic cirrhosis remains to be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Under hepatic pathological conditions, an aberrant activation of β -catenin was evident in chronic inflammation, steatosis, fibrosis, and subsequently tumors of the liver [ 18 , 19 ]. Another “active player”, COX-2, a key protein involved in the inflammation process [ 20 ], had also been suggested to play important roles in the relationship between inflammation and cancer. Studies had shown that the expression of COX-2 in para-carcinoma tissues was higher than that of tumor tissues and was also positively correlated with the degree of differentiation for liver tumor, suggesting a promoting role in the carcinogenesis of early stage [ 21 ].…”
Section: Introductionmentioning
confidence: 99%